Strategic plan of Tagum City Employees Cooperative (TACECO) for 2006-2010 - Delgado, Jetzyl N. (School of Management, University of the Philippines Mindanao, 2006)
The Tagum City Employees Cooperative (TACECO) is a Multi-purpose Non-agricultural cooperative with 247 members in 2005. TACECO aims to strengthen its financial capability, to co-exit with one another and to provide for the needs of its members through credit. The share capital has grown from P60,000.00 in 1994 to P3,533,507.54 as of August 2005. This paper aims to provide TACECO practical strategies for the sustainability of the organization, considering internal and external forces. The strategic framework of Fred R. David and Miguel D. Soledad, shown in Chapter 1, guided the analysis of the operations of TACECO. The approaches in gathering the necessary data involve interviews and inquiries from the BOD, staff and members of TACECO. Secondary information was also gathered from the internet and published materials. Based on the internal and external analyses, the strengths, weaknesses, opportunities and threats of TACECO were identified, which are the bases in generating strategic options. The following are the internal and external factors affecting TACECO: STRENGHTS: 1. Strong linkage with LGU departments; 2. Regular orientation thus increasing membership; 3. Increasing capital share; 4. Insured loan payments; 5. Satisfied members and has employed incentive schemes WEAKNESSES: 1. Not well-communicated objectives; 2. Slow service due to manual bookkeeping and database; 3. Deteriorating operational efficiency; 4. Unemployed performance evaluation measures; 5. No manager; lacks monitoring and control systems; 6. Did not consider itself as a savings cooperative. OPPORTUNITIES: 1. Strict implantation of SCA and COOP-PESOS; 2. GRDP of Region XI expected to increase; 3. Increasing economic needs of families; 4. Easy access to information; computerization; 5. Possible tie-up or linkage with best cooperatives. THREATS: 1. Change of LGU administration may discourage membership; 2. Withdrawal of capital share due to migration; 3. Non-payment of delinquent loans; 4. Increased prices of softwares and technological equipment; 5. Available banking and credit institutions. The general options from the above-mentioned factors are: Regular performance standards evaluation using COOP-PESOS, computerization of accounting system, institutionalization of the organization, strengthen capital base through deposits, establish strategic alliances with cooperatives and organizations, training and product innovation, improve operational efficiency, intensify recruitment through regular orientation. Among the options, the top three proposed strategies are: 1. Improve operational efficiency; 2. institutionalization of the cooperative; 3. strengthening of capital base.